Primary Non-refluxing Megaureter: Analysis of Risk Factors for Spontaneous Resolution and Surgical Intervention - Dekirmendjian, Adriana; Braga, Luis H. (Frontiers in Pediatrics, 2019)
Background: The risk of febrile urinary tract infection (fUTI) in children with primary non-refluxing megaureter (PM) has been extensively studied in the literature, however, a paucity of information exists regarding risk factors for surgical intervention and spontaneous resolution. We sought to analyze data from our prospectively collected PM cohort to determine risk factors that would predict surgery and resolution in this population. Methods: Patients with PM were identified from our prospectively-collected prenatal hydronephrosis (HN) database from 2008-2017. Primary outcomes included surgical intervention and hydroureter resolution. Spontaneous resolution was defined as ureteral dilation <7 mm at last follow-up. Age at presentation, gender, development of fUTI, HN grade [low (SFU I/II) vs. high (SFU III/IV)], anteroposterior diameter (APD) measurements and ureteral diameter at baseline and last follow-up were recorded. Univariate and multivariable analyses (binary logistic and Cox regression) were performed. Results: Of 101 patients, 86 (85%) were male, and 80 (79%) had high grade HN. Median age at baseline and last follow-up were 2 (0-23) and 29 (2-107) months, respectively. Overall, 23 (23%) patients underwent surgery at a median age of 22 (3-35) months. Mean ureteral diameter was larger in surgical patients versus those treated non-surgically (14+4mm vs.11+3mm; p<0.01). Of the 78 (77%) non-surgical patients, 43(55%) showed resolution of their ureteral dilation at a median age of 24(4-56) months. Survival analysis demonstrated that 12 patients resolved by year 1, 22 by year 2, 30 by year 3, 40 by year 4, and 43 by year 5. However, when considering resolution as APD <10mm, 62(79%) children resolved their HN by last follow-up (29 months). Univariate and multivariable analyses (Table 1) revealed that high-grade HN at baseline, development of fUTI, and ureteric dilation ≥14mm were significant risk factors for surgical intervention. Cox regression (Figure 2) found that ureteral dilation <11mm was the only independent risk factor significantly associated with PM resolution (Table 2). Conclusion: Patients with PM and high-grade HN, as well as individuals with ureteral dilation ≥14mm and fUTI were more likely to undergo surgical intervention. Ureteral dilation <11 mm was the only independent risk factor significantly associated with spontaneous resolution of PM.